sebuah UJI KOMBINASI EKSTRAK WANGI LEMONGRASS DAN DAUN SIRSAK TERHADAP CACING ARMY (Spodoptera litura) PADA TANAMAN SAWI - Wendi Akbar Wiranata; Djamilah; Tri Sunardi (BPFP Universitas Bengkulu, 2023)
Efficacy of Lemongrass and Soursop Leaf Extracts for Controlling ArmywOrm (Spodoptera litura J.E. Smith) Infestation in Green Mustard Cultivation]. Employing vegetable insecticide as a primary measure for controlling armyworms (Spodoptera litura) represents an environmentally friendly strategy to enhance yield. This research, conducted between December and February 2021 at the Plant Protection Laboratory and Plant Protection Gauze House, Faculty of Agriculture, Bengkulu University, aimed to determine the effective concentration of vegetable insecticides for managing armyworms infestation in green mustard. A randomized complete design (CRD) with six treatments and five replications was employed for the efficacy test. The treatments comprised: control, lemongrass extract, soursop leaf extract, lemongrass and soursop leaves extracts in a 1:1 ratio, lemongrass and soursop leaves extracts in a 1:2 ratio, and lemongrass and soursop leaves extracts in a 2:1 ratio. The results demonstrated that both lemongrass and soursop leaf extracts, either individually or in combination, effectively controlled S. litura larvae. Notably, an 8% concentration of citronella extract exhibited the highest mortality rate at 60%, with soursop leaves achieving 53.3%. In combination extracts, lemongrass and soursop leaves extracts in 1:1 and 2:1 ratio resulted in a 43.4% larvae control, while the ratio of lemongrass 1:2 to soursop leaves achieved a 36.6% larvae control. Overall, the research underscores the potential of vegetable insecticides, specifically lemongrass and soursop leaf extracts, as viable components of integrated pest management strategies to maintain crop yield in green mustard cultivation.